High dielectric permittivity by ionic space charge polarization in polyethylene oxide - Kliem, Herbert; Wagner, Achim (2001 annual report, 2002)
The nominal static dielectric permittivity of polyethylene oxide can be as high as /spl epsi//sub r/'=150000. The permittivity depends strongly on frequency, humidity absorption, sample thickness, temperature, bias field, and dopant concentration. This behavior is due to an ionic space charge movement with blocking and accumulation of ions at the electrodes. The space charge polarization is modeled in the following way: mobile positive ions fluctuate in a three dimensional multi-well potential by thermal activation. A negative background charge of the same magnitude provides overall charge neutrality. To calculate the local field at each well, the Coulomb interactions between the ions and the image charges in the electrodes are considered. A Monte Carlo simulation yields the experimental results with respect to the investigated parameters. In the time domain a Kohlrausch behavior of the polarization current j/spl sim/t/sup -1.2/ is computed due to the attraction between the ions in the material and their image charges in the electrodes.
Elektronische Reproduktion der Druckausgabe
Gesehen am 15.01.2020